Socioeconomic Factors Affect Disparities in Access to Liver Transplant for Hepatocellular Cancer - Linda L. Wong; Brenda Y. Hernandez; Cheryl L. Albright (Journal of Transplantation)
Objective. The incidence/death rate of hepatocellular cancer (HCC) is increasing in America, and it is unclear if access to care contributes to this increase. Design/Patients. 575 HCC cases were reviewed for demographics, education, and tumor size. Main Outcome Measures. Endpoints to determine access to HCC care included whether an eligible patient underwent liver transplantation. Results. Transplant patients versus those not transplanted were younger (55.7 versus 61.8 yrs, P<0.001), males (89.3% versus 74.4%, P=0.013), and having completed high school (10.1% versus 1.2%, P=0.016). There were differences in transplant by ethnicity, insurance, and occupation. Transplant patients with HCC had higher median income via census classification ($54,383 versus $49,383, P=0.046) and self-reported income ($48,948 versus $38,800, P=0.002). Differences in access may be related to exclusion criteria for liver transplant, as Pacific Islanders were more likely to have tumor size larger than 5 cm compared to Whites and have BMI > 35 (20.7%) compared to Whites (6.4%) and Asians (4.7%). Conclusions. Ethnic differences in access to transplant are associated with socioeconomic status and factors that can disqualify patients (advanced disease/morbid obesity). Efforts to overcome educational barriers and screening for HCC could improve access to transplant.